Modelling of NO and HC removal by non-thermal plasmas - Orlandini, Igor; Riedel, Uwe (Combustion theory and modelling, 2006)
Public concern about the environmental situation creates strong restrictions on the purity of exhaust gases in various polluting industrial enterprises. A promising method of gas cleaning is the use of pulsed corona discharges. In these devices, short pulses at high frequency allow one to increase the energy input and radical production for subsequent transformation of toxic pollutants (NO x , SO2, C x H y , etc). For a better understanding and optimization of the possible applications of this technique it is necessary to develop models for the underlying physical and chemical processes which are responsible for the removal of pollutants. In this work, we have theoretically investigated the removal of NO and the effect of ethane and propene on NO removal by non-thermal plasma discharges at low temperature (373 K) and at atmospheric pressure. The model takes into account the production of radicals after every discharge and the subsequent removal of NO and HC by radicals. Reaction flow analysis reveals the characteristic differences of NO reactions in the presence of unburned alkanes and alkenes. The results of our numerical simulations show good agreement with experimental data published in the literature.